Survei Pembelajaran Kearifan Lokal di Taman Kanak-Kanak Se-Provinsi Daerah Istimewa Yogyakarta - Pamungkas, Joko; Syamsudin, Amir; Harun, Harun; Sudaryanti, Sudaryanti (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2019)
Local wisdom is something very important to be cultivated as an effort to inculcate the values contained in it. This needs to be instilled from an early childhood education. The purpose of this study was to describe the implementation of learning local wisdom in kindergarten throughout the province of DIY. The research method used is a survey. The results of the study show that the wealth of local wisdom has not been used optimally for the stimulation process of early childhood development. The skills of taste such as carving, playing gamelan and tambourines performed by children hardly occur in the implementation of early childhood learning. However, the skills of painting skills get the best portion of early childhood learning in all districts / cities in DIY. Likewise, the introduction of names for nuclear family members, large families, types of work, traditional games, traditional ceremonies, names of animals, plants, and time markers have been well implemented in the process of early childhood learning. Learning local wisdom can stimulate children’s full potential.